PENGUATAN EKONOMI DESA CIPAJANG MELALUI IMPLEMENTASI PRAKTIK AKUNTANSI BERKELANJUTAN - Hamzah, Amir; Wiharno, Herma; Suhendar, Dadang; Purnama, Dendi (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
Community service is an important effort to improve the quality of life and the economy of the community, especially in rural areas. This activity was conducted in Cipajang Village, Banjarharjo District, Brebes Regency, Central Java, with the aim of enhancing the understanding of micro, small, and medium enterprises (MSMEs) participants about basic accounting and financial management. The partners in this community service initiative consisted of 30 local MSME participants who actively engaged in the training. The implementation method included delivering theoretical material on basic accounting principles, practical sessions on transaction recording, and evaluations through pre-tests and post-tests to measure participants' knowledge improvement. The results indicated that the training successfully increased participants' knowledge, with average post-test scores significantly higher than those of the pre-tests. Additionally, feedback from participants showed a high level of satisfaction and a strong desire to attend follow-up training sessions. Despite some challenges, such as time constraints, this activity is expected to positively impact the economic empowerment of the village community. Through this program, it is hoped that MSME participants in Cipajang Village can become more self-sufficient and enhance their competitiveness in the local market. Keywords: Community service; accounting; MSME participants; Cipajang Village; financial.